MELAYANI YESUS YANG HADIR TERSAMAR DALAM DIRI ORANG MISKIN: SEBUAH TELAAH SPIRITUALITAS TERHADAP PELAYANAN IBU TERESA DARI KALKUTA KEPADA KAUM MISKIN - Yabarmase, Agustinus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2013)
The charity work of Mother Teresa of Calcutta to the poorest of the poor cannot be separated from her appreciation about the words of Jesus: “Amen, I say to you, whatever you did for one of these least brothers of mine, you did for me” (Mat. 25: 40). With these Jesus’ words, Mother Teresa realized that Jesus is present within each person. More specifically, the presence of Christ is only vaguely perceived within the poor. Therefore, Mother Teresa always dedicated her life for the service to the poor both in India and in other countries where the Missionaries of Charity work